HAFALAN SURAH AL KAFIRUN MELALUI GERAK KINESTETIK ANAK USIA DINI - Fu’ad Arif Noor; Astuti Marheni Sri Prasetyaningsih (STPI Bina Insan Mulia Yogyakarta, 2021)
This research was conducted to determine learning through the kinesthetic motion method in increasing learning activities and the ability to memorize letters of Al Kafirun in BA Aisyiyah Kwaren II, Ngawen, Klaten. The method used is the method of action research (action research) and the data collection technique was carried out by observing the activities of students and teachers, tests, partner teacher responses, and monitoring classroom observations. The results showed that learning through the kinesthetic motion method paid more attention and interest to students. Students' activity increased from cycle 1 to cycle 2. This was evidenced by students being more active, more daring to ask questions, starting to increase their ability to memorize letters Al Kafirun, daring to try to memorize letters Al Kafirun either with or without teacher guidance, and more active in learning. The results of the assessment of the performance of the memorizing ability of Al Kafirun's letters increased, namely; Pre-cycle the average value of students is 56, cycle I is 69 and cycle II becomes 82. Furthermore, based on the responses of partner teachers in implementing learning using modeling techniques, it becomes more fun, easier to understand, makes students want to be more active and creative, and not confusing.